Characterization and recovery of areas with mining co-products in paraíba semiarid. Increment of litter (Research, Society and Development, 2022)
The different climatic factors and misguided human actions can contribute to the significant increase in the degradation process. The litter transposition acts as a technique to facilitate the recovery of degraded areas. The objective of this study was to promote the recovery process of areas degraded by the deposition of mining byproducts in the semi-arid region of Paraíba through native species of the Caatinga biome and also through the use of actions that allow the recovery and preservation of the biome, due to the exploitation of natural resources in a sustainable way. The work was developed in the area where the co-products were deposited, in the courtyard of the company Mineração Pedra Lavrada, municipality of Santa Luzia, Paraíba, during the period from August 2018 to July 2019. Initially, 12 simple soil samples were collected, to form four composite samples to represent the area, after physical-chemical analyses of the substrate were made and the oldest area to install the experiment was defined. The burlap was collected from sites of native vegetation. The randomized block design with four repetitions and six treatments: control and incorporating 2.5, 5.0, 7.5, 10.0 and 12.5% of burlap to the substrate. The vegetative variables, temperature and humidity of the substrate were evaluated monthly. There was no significant interaction for humidity between treatments and months of the experiment. There were statistical differences for temperature between the months evaluated. There were no positive results in the germination of seeds from burlap incorporated to the substrate. The transposition of burlap was not efficient during the months evaluated, requiring a longer period of evaluation for more satisfactory results.